2004
DOI: 10.1159/000076479
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Treponema pallidum</i> in Skin Lesions of Secondary Syphilis and Characterization of the Inflammatory Infiltrate

Abstract: Background: Syphilis is an ancient sexually transmitted disease. However, the pathogenesis of mucocutaneous lesions of secondary syphilis is not completely understood. Methods: We analyzed the presence of Treponema pallidum in formalin-fixed, paraffin-embedded biopsy specimens from mucocutaneous lesions of secondary syphilis using highly sensitive nested polymerase chain reaction (PCR). The inflammatory infiltrates from the same specimens are also characterized using immunohistochemical methods. Results and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 3 publications
5
29
0
4
Order By: Relevance
“…Histological patterns of cutaneous syphilis have been characterized extensively, and, during the past decade, immunohistological techniques have identified the nature of inflammatory cells [24,25]. Nevertheless, compared with many other common inflammatory disorders, little is known about the local immune responses to T. pallidum in skin and other body sites [26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Histological patterns of cutaneous syphilis have been characterized extensively, and, during the past decade, immunohistological techniques have identified the nature of inflammatory cells [24,25]. Nevertheless, compared with many other common inflammatory disorders, little is known about the local immune responses to T. pallidum in skin and other body sites [26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, T cells and macrophages are found in rabbit dermal lesions (276), as well as in human primary chancres (90,314,325) and secondary lesions (90,198,325,333 (198). mRNA for the cytokines gamma interferon (IFN-␥) and IL-2, which function to activate macrophages and stimulate proliferation of T cells, respectively, is also found in primary and secondary lesions (323).…”
Section: Immune Clearancementioning
confidence: 99%
“…In molecular studies, T. pallidum DNA was detected in lesional follicles, providing further support for a specific immunological reaction to T. pallidum antigens [24]. A recent Chinese study demonstrated the presence of T. pallidum in mucocutaneous lesions of secondary syphilis using highly sensitive nested polymerase chain reaction [25]. If the papular syphilides are located in intertriginous areas, maceration can lead to flat, damp lesions, the so-called condylomata lata.…”
Section: Clinical Features Of Casesmentioning
confidence: 99%